Measurement and evaluation of radar cross section for furniture in an indoor propagation channel - M. M. Maw; P. Supanakoon; S. Promwong; J. Takada (My University, 2014)
Abstract. This paper has attempted to evaluate the radar cross section (RCS) of two furniture items in an indoor environment in a frequency range of 3–7 GHz of the ultra-wideband (UWB) range. The RCS evaluation is achieved through an extended version of the radar equation that incorporates the channel transfer function of scattering. The time-gating method was applied to remove the multipath effect, a phenomenon which typically occurs in the indoor environment. Two double-ridged waveguide horn antennas for both vertical and horizontal polarizations were used to obtain the transfer function of scattering of the furniture prior to analysis in order to derive their bistatic RCS. The RCS results validate the applicability of the proposed extended radar equation to the indoor propagation prediction.
Keywords: Radar cross-section; Wideband; Millimeter-Wave Propagation and Modeling